Facebook Sebagai Media Komunikasi dan Informasi bagi Generasi Milenial di Desa Man-Gega Kabupaten Kepulauan Sula Maluku Utara - Sindi Sundari Rante Pasang (GLOBAL SCIENTS PUBLISHER, 2026)
The development of information and communication technology has transformed how people interact and access information, with Facebook remaining a widely used platform. This study examines its role as a communication and information medium among millennials in Man-gega Village, Sula Islands Regency, North Maluku. Using a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation, and analyzed based on the Uses and Gratifications Theory. Findings reveal that Facebook serves as a relevant tool for obtaining information on village activities, education, and economic opportunities, as well as for maintaining social connections regardless of distance. While it offers benefits such as faster information sharing and broader social networks, it also presents challenges including over-reliance, misinformation, and reduced face-to-face interaction. Overall, Facebook remains an important and effective medium for meeting the communication and information needs of local millennials.